Regulatory Cell Therapy in Organ Transplantation: Achievements and Open Questions - Fortunato, Marta; Morali, Konstantina; Passeri, Laura; Gregori, Silvia (Frontiers in Immunology, 2021)
The effective development of innovative surgical applications and immunosuppressive agents have improved remarkable advancements in solid organ transplantation. Despite these improvements led to prevent acute rejection and to promote short-term graft survival, the toxicity of long-term immunosuppression regiments has been associated to organ failure and chronic graft rejection. The graft acceptance is determined by the balance between the regulatory and the alloreactive arm of the immune system. Hence, enhance regulatory cells leading to immune tolerance would be the solution to improve long-term allograft survival which, by reducing the overall immunosuppression, will provide transplanted patients with a better quality of life. Regulatory T cells (Tregs), and regulatory myeloid cells (MRCs), including regulatory macrophages and tolerogenic dendritic cells, are promising cell populations for restoring tolerance. Thus, in the last decade efforts have been dedicated to apply regulatory cell-based therapy to improve the successful rate of organ transplantation and to promote allogeneic tolerance. More recently, this approach has been translated into clinical application. The aim of this review is to summarize and discuss results on regulatory cell-based strategies, focusing on Tregs and MRCs, in terms of safety, feasibility and efficacy in clinical studies of organ transplantation.